Loss of consciousness and altered mental state predicting depressive and post-concussive symptoms after mild traumatic brain injury. (3rd July 2019) - Roy, Durga; Peters, Matthew E.; Everett, Allen; Leoutsakos, Jeannie-Marie; Yan, Haijuan; Rao, Vani; Bechtold, Kathleen; Sair, Haris; Van Meter, Timothy E.; Falk, Hayley; Vassila, Alexandra; Hall, Anna; et al.
ABSTRACT: Objective : Limited studies exist on the association between loss of consciousness (LOC) and altered mental state (AMS) and development of depressive and post-concussive symptoms within six months after mild traumatic brain injury (mTBI). We tested the hypothesis that presence of both LOC and AMS predict the highest risk of symptoms within the first six months post-mTBI compared to either variable alone, and that LOC alone is more strongly associated with these symptoms. Research design : We analyzed data from 407 subjects with mTBI from the Head injury S erum M arkers for A ssessing R esponse to T rauma (HeadSMART) cohort, a prospective cohort of patients post-TBI presenting to two urban emergency departments. Results : There were higher rates of depressive (44%) and post-concussive symptoms (54%) at 1 month post-injury, among participants with both LOC and AMS compared to other groups. AMS was associated with depressive symptoms at one and six months (OR = 1.59, p = .038; OR = 1.60; p = .060) and post-concussive symptoms at one month (OR = 1.56, p = .053). LOC was associated only with post-concussive symptoms at one month (OR = 1.55;p = .048). Among those without LOC, AMS was associated with depressive symptoms at one month (OR = 2.24; p = .028). Conclusions : AMS predicts post-mTBI depressive symptoms both in the acute and chronic mTBI phases whereas LOC is a more sensitive predictor of post-concussive symptoms in the acute mTBI period.